Peran Kepribadian terhadap Perilaku Social Loafing pada Mahasiswa (The Influence of Personality Traits on Social Loafing Behavior among College Students) - Fitriani, Nisa (Happiness: Journal of Psychology and Islamic Science, 2025)
The purpose of this study was to determine the effect of personality (including extraversion, agreeableness, conscientiousness, openness to experience, and neuroticism) on social loafing. The research method chosen is quantitative. The research sample comprised 222 college students at UIN Syekh Wasil Kediri, selected using an accidental sampling technique. The instruments used were the Big Five Inventory, adapted by Agung et al. (2019), and the social loafing scale, adapted by Ramdhani (2012). The test results showed F = 7.32 with a significance of p = 0.00 (<0.01), meaning that the variables of extraversion, neuroticism, conscientiousness, agreement, and openness to experience simultaneously influence social loafing. The next result, partially, the dimensions of agreement (β = –0.196; p = 0.005) and conscientiousness (β = –0.276; p = 0.000) had a significant negative effect on social loafing. This indicates that the higher the two dimensions, the lower the tendency of students' social loafing behavior.